Quantification of hydroxyl exchange of D‐Glucose at physiological conditions for optimization of glucoCEST MRI at 3, 7 and 9.4 Tesla. (17th July 2019) - Zaiss, Moritz; Anemone, Annasofia; Goerke, Steffen; Longo, Dario Livio; Herz, Kai; Pohmann, Rolf; Aime, Silvio; Rivlin, Michal; Navon, Gil; Golay, Xavier; Scheffler, Klaus
Abstract : Aims: To determine individual glucose hydroxyl exchange rates at physiological conditions and use this information for numerical optimization of glucoCEST/CESL preparation. To give guidelines for in vivo glucoCEST/CESL measurement parameters at clinical and ultra‐high field strengths. Methods: Five glucose solution samples at different pH values were measured at 14.1 T at various B1 power levels. Multi‐B1 ‐Z‐spectra Bloch‐McConnell fits at physiological pH were further improved by the fitting of Z‐spectra of five pH values simultaneously. The obtained exchange rates were used in a six‐pool Bloch‐McConnell simulation including a tissue‐like water pool and semi‐solid MT pool with different CEST and CESL presaturation pulse trains. In vivo glucose injection experiments were performed in a tumor mouse model at 7 T. Results and discussion: Glucose Z‐spectra could be fitted with four exchanging pools at 0.66, 1.28, 2.08 and 2.88 ppm. Corresponding hydroxyl exchange rates could be determined at pH = 7.2, T  = 37°C and 1X PBS. Simulation of saturation transfer for this glucose system in a gray matter‐like and a tumor‐like system revealed optimal pulses at different field strengths of 9.4, 7 and 3 T. Different existing sequences and approaches are simulated and discussed. The optima found could be experimentally verified in an animal model at 7 T. Conclusion: For the determined fast exchange regime, presaturation pulses in the spin‐lock regime (long recover time, short yet strong saturation) were found to be optimal. This study gives an estimation for optimization of the glucoCEST signal in vivo on the basis of glucose exchange rate at physiological conditions. Abstract : Using ultra‐high field strength, multiple saturation powers and multiple pH values, determination of the glucose hydroxyl exchange rates by chemical exchange saturation transfer (CEST) at physiological conditions was made possible. These insights were used to optimize the dynamic glucose enhancement in glucoCEST injection studies in vivo.